Analysis of Mechanical and Electrical Load Variations on Energy Output Performance of a Piezoelectric Floor Prototype - Tirta, Bram; Gerhana; Zanu Saputra; Peprizal (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2026)
This study aimed to investigate the influence of mechanical and electrical load variations on the output characteristics of a piezoelectric floor prototype designed for small-scale energy harvesting applications. The prototype consisted of 128 lead zirconate titanate (PZT)-based piezoelectric elements connected in a parallel configuration to enhance the total current output. Experimental tests were conducted using two user mass variations, 69 kg and 98 kg, to represent differences in the applied mechanical pressure on the floor surface. Two types of electrical loads were examined: a simple 1 ? resistive load and a charging circuit comprising a bridge rectifier, a boost converter, and a TP4056 module for charging a 3.7 V nominal Li-ion battery. The results indicated that an increase in mechanical load led to a higher output current, with average values of 3.67 mA and 11.67 mA for 69 kg and 98 kg tests under resistive load conditions, respectively. In contrast, the average current decreased to 1.06 mA and 4.12 mA when the charging circuit was applied, due to conversion and regulation losses. Overall, the system demonstrated functional capability in generating electrical energy and charging low-power storage devices, highlighting its potential as an alternative piezoelectric-based renewable energy source.